2012
DOI: 10.1007/s00216-012-6075-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a monolithic, micro-immobilised enzyme reactor via click-chemistry

Abstract: An immobilised enzyme reactor (IMER) in the form of capillary monolith was developed for a micro-liquid chromatography system. The plain monolith was obtained by in situ thermal copolymerisation of glycidyl methacrylate and ethylene dimethacrylate in a fused silica capillary (200 × 0.53 mm ID) by using n-propanol/1,4-butanediol as porogen. The enzyme, α-chymotrypsin (CT), was covalently attached onto the monolith via triazole ring formation by click-chemistry. For this purpose, the monolithic support was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Compared to other previously published work on IMER columns, the NAS-AAm-Bis column features mild fabrication condition and an open tubular inner structure with higher protein sequence coverage as observed with BSA analysis [28,29]. We further applied IMER digestion to more complex samples followed by LC-ESI-Orbitrap detection to test if IMER digestion can be applied to large-scale proteomics studies.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other previously published work on IMER columns, the NAS-AAm-Bis column features mild fabrication condition and an open tubular inner structure with higher protein sequence coverage as observed with BSA analysis [28,29]. We further applied IMER digestion to more complex samples followed by LC-ESI-Orbitrap detection to test if IMER digestion can be applied to large-scale proteomics studies.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the final substrate conversion increased with increasing the feed flow rate and substrate feed concentration due to the increase of the interaction between the substrate and the enzymatic monolith reactor. The preparation of a monolithic-immobilized enzyme reactor by click-chemistry for micro-LC was recently reported [22]. It involved the preparation of a poly(GMA-co-EDMA) monolith via in situ thermal polymerization in capillary format.…”
Section: Ppf Involving Click Coupling Of Monolithsmentioning
confidence: 99%
“…Soybean trypsin inhibitor was clicked on this support after conjugation through the N ‐hydroxysuccinimide ester of 4‐pentynoic acid to produce an affinity sorbent for trypsin. Porous (GMA‐co‐EDMA) monolithic capillary columns were used to click an alkyne‐carrying enzyme derivative (α‐chemotrypsin) to prepare immobilized enzyme reactors . In both cases, biomolecules have to be derivatized with heterobifunctional reagents carrying the alkyne moiety.…”
Section: “Clicked” Stationary Phases and Their Applications In Varioumentioning
confidence: 99%
“…Such reactions afford high yields and can be carried out in various solvents such as aqueous solutions at room temperature. Due to these numerous benefits, "click reactions" have received more and more interest in many areas such as nanotechnology [2,3], bioconjugation [4,5], DNA functionalization [6,7], surface modification [8][9][10], polymers [11][12][13][14], and others [15][16][17]. Over the last 10 years, click chemistry has also spread to separative sciences and more particularly for the preparation of chromatographic materials [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation